POTENSI PENGEMBANGAN PETERNAKAN AYAM RAS PETELUR DI KABUPATEN HALMAHERA BARAT - Pelafu, Fony; Najoan, M; Elly, F H (ZOOTEC, 2018)
THE DEVELOPMENT POTENTIAL OF LAYER POULTRY IN WEST HALMAHERA REGENCY.The objective of this study was to analyse the potential and constraints and strategic priority of laying hen development. Respondents were chosen purposively involving farmers, policy makers and related stakeholders. Breeders weregenerally in their productive age with medium education levels, the breeders who were not been trained and the breeders who had no breeding experience. Majority of breeders had the profession as farmers. The ownership status of the farm business belongs to both group and private, and most of them made their livestock business as a sideline to add their income. Management of cultivation wasnot done properly so that the population fluctuated, and productivity was very low. The main strength was business capital support from local government and egg marketing was relatively easy. The main weakness was the lack of information. The main opportunity was the government policy supporting the livestock industry in conducive situation and the biggest threat was the price of feed tending to fluctuate. The alternative strategy achieved were increasing the market share to achieve market leader position through local government policy, improving the quality of human resources through mentoring and assistance to increase productivity, providing livestock production facilities, especially feed in the area by utilizing available local raw materials, and establishing cooperation through partnership between farmers and the private company. Based on QSPM analysis, the priority of strategy chosen was to establish cooperation through partnership between breeder and private sector / Animal Husbandry Company with the highest total TAS value of 5,353.Â Keywords: layerdevelopment strategy, West Halmahera regency potential.